2020
DOI: 10.3390/chemistry2040056
|View full text |Cite
|
Sign up to set email alerts
|

New Antimicrobial Strategies Based on Metal Complexes

Abstract: Traditional organic antimicrobials mainly act on specific biochemical processes such as replication, transcription and translation. However, the emergence and wide spread of microbial resistance is a growing threat for human beings. Therefore, it is highly necessary to design strategies for the development of new drugs in order to target multiple cellular processes that should improve their efficiency against several microorganisms, including bacteria, viruses or fungi. The present review is focused on recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
132
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(134 citation statements)
references
References 176 publications
(289 reference statements)
2
132
0
Order By: Relevance
“…It is well known that phenolic acids and flavonoids nullify the potential of the internal bacterial membrane, decrease the production of ATP, and inhibit DNA gyrase involved in the synthesis of bacterial DNA and RNA which leads to the inhibition of bacterial viability [ 62 , 63 ]. Interestingly, numerous researchers improved the toxic effects of minerals such as iron, phosphorus, cooper, and zinc on both Gram-positive and Gram-negative bacteria [ 58 , 64 , 65 ]; therefore, the richness in macro- and microelements gives propolis an additional potential antibacterial.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that phenolic acids and flavonoids nullify the potential of the internal bacterial membrane, decrease the production of ATP, and inhibit DNA gyrase involved in the synthesis of bacterial DNA and RNA which leads to the inhibition of bacterial viability [ 62 , 63 ]. Interestingly, numerous researchers improved the toxic effects of minerals such as iron, phosphorus, cooper, and zinc on both Gram-positive and Gram-negative bacteria [ 58 , 64 , 65 ]; therefore, the richness in macro- and microelements gives propolis an additional potential antibacterial.…”
Section: Resultsmentioning
confidence: 99%
“…ese modified dinuclear complexes were suspected to possess better activity due to their structural characteristics. e ligands found in these complexes have planar aromatic rings (the pyridyl moieties and the aromatic ether-amine central ring) which may have induced better affinity to physically bind to biological molecules [15]. Furthermore, the dinuclear nature of complexes 3 and 4 may have greatly influenced their antibacterial properties.…”
Section: Mic Assaymentioning
confidence: 99%
“…Metal-based drugs have attracted enormous attention due to their pharmacological effects, which includes anticancer, anti-inflammatory, antioxidant, and antimicrobial activities (Mjos and Orvig, 2014;Anthony et al, 2020). In fact, inorganic medicinal chemistry has advanced in recent years, providing an alternative therapeutic approach to the purely organic antimicrobial agents (Lemire et al, 2013;Viganor et al, 2017;Claudel et al, 2020). Several studies have shown that 1,10-phenanthroline (phen) and its derivatives, as ligands coordinated to transition metals, exhibit potent antifungal activity against Candida albicans and non-albicans Candida species, such as C. tropicalis, C. krusei, C. glabrata, and C. haemulonii (Geraghty et al, 2000;McCann et al, 2000McCann et al, , 2012Coyle et al, 2003;Hoffman et al, 2015;Gandra et al, 2017Gandra et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%